Pendekatan Inovatif dalam Manajemen Ternak: Analisis Perbandingan Good Farming Practices (GFP) dan Inseminasi Buatan (IB) Berbasis Biologi Molekuler: Innovative Approaches in Livestock Management: A Comparative Analysis of Good FarmingPractices and Molecular Biology Based Artificial Insemination - Nicky, Dhea; Mustikaningtyas, Dewi; Anggraito, Yustinus Ulung (BPFP Universitas Bengkulu, 2025)
Livestock farming is an important sector in meeting the food needs of the community, especially for animal protein from meat and dairy products. Although livestock farming has great potential, livestock productivity still faces significant challenges, including inadequate husbandry systems, technological limitations, and a lack of understanding of reproductive management. In an effort to improve productivity, two approaches that can be applied are Good Farming Practices (GFP) and Artificial Insemination (AI) based on molecular biology. GFP includes principles of feed management, sanitation, livestock health, and a good environment, which are expected to improve livestock welfare and the quality of production results. On the other hand, IB uses advanced technology to improve the genetic quality of livestock and enhance reproductive efficiency, particularly with the integration of molecular biology techniques. This study aims to compare the effectiveness of both approaches in improving livestock productivity. By applying GFP and IB synergistically, it is hoped that the increasing market demand can be met without neglecting animal welfare aspects.